ANALISIS PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PERUSAHAAN JASA SUB SEKTOR KONTRUKSI DI BURSA EFEK INDONESIA - Fazza Himawan; Rivera Pantro Sukma (LPPM Universitas Asa Indonesia, 2019)
The purpose of this study was to analyze the effect of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Return On Assets. The population in this study are construction sub sector companies listed on the Indonesia Stock Exchange in 2014-2018. The number of samples in this study were 8 companies for 5 years of observation. The method used was purposive sampling, with a total of 40 financial statements. Testing the hypothesis in this study using multiple regression analysis, assisted by Eviews software version 11.0. The results of this study stated that the Current Ratio partially significant effect on Return On Assets, while Debt to Equity Ratio and Total Asset Turnover have significantly effected Return On Assets. Then, Current Ratio, Debt to Equity Ratio, and Total Asset Turnover, Simultaneously, have influenced Teturn On Asset, significantly. Based on Determination Coefficient Test results it is known that the R square value is 0.564 or 56.4%, which shows that 56.4% Return On Assets can be explained by Current Ratio, Debt to Equity Ratio, and Total Asset Turnover,. While the rest of 43.6% is explained by other variables that not analyzed in this study. For company management, they should be able to take advantage of the level of Total Asset Turnover to be able to increase sales in achieving corporate profit. By increasing the Total Asset Turnover (TATO), the trust of investors and creditors will be increased, at the same time it takes extension of cooperation contract with the prospective companies.